+0  
 
0
41
1
avatar+16 

Solve for e

 

g/e^2 - r = m- y

 

lightningpercy3  Nov 20, 2018
 #1
avatar+92808 
+1

g/e^2 - r = m- y     add r to both sides

 

g      =   m - y  + r

__       _________       we can "flip" both fractions and still keep equality...so...

e^2          1

 

 

 

e^2    =      1

____       ________          multiply both sides by g

g             m - y + r

 

 

e^2     =    g   / [ m - y + r ]        take both roots

 

 

e   =  ±√  [ g   / ( m - y + r )  ] 

 

 

 

cool cool cool

CPhill  Nov 20, 2018

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.